Sosialisasi Pemberdayaan Perempuan dan Pendidikan Anak untuk Mewujudkan Desa Ramah Perempuan dan Anak di Desa Pemepek - Istinawati, Baiq; Syawahid, Muhammad; Muliadi, Erlan; Raehanah; Syukriati (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The potential of women is often overlooked, and even the empowerment of women's abilities is very limited. Pemepek Village, the location of the UIN Mataram Participatory Field Study (KKP), is one of the villages that is striving to implement the Women-Friendly Village program. This activity was held in the hall of the Pemepek village office in Central Lombok with participants consisting of PKK mothers and junior high and high school students as well as teenagers in the village of Pemepek. The method used in this community service activity was the Participatory Action Research (PAR) method, which consists of 3 stages, namely the preparation stage, the implementation stage, and the evaluation stage. In the preparation stage, problem identification activities were carried out by mapping the targets, coordinating with partners, and preparing tools and materials. In the implementation stage, material delivery, discussions, and question and answer sessions were carried out. The evaluation stage involved administering comprehension tests to evaluate participants' understanding of women's empowerment and children's education. The result of this activity was the successful delivery of material related to women's protection and children's education, with participants' comprehension evaluated as very good. This activity received a positive response from participants and is expected to be one of the steps taken by the village government to create a women and child-friendly village.